State of the art of sepsis care for the emergency medicine clinician - Namita Jayaprakash; Nima Sarani; H. Bryant Nguyen; Chad Cannon (Journal of the American College of Emergency Physicians Open)
Abstract Sepsis impacts 1.7 million Americans annually. It is a life‐threatening disruption of organ function because of the body's host response to infection. Sepsis remains a condition frequently encountered in emergency departments (ED) with an estimated 850,000 annual visits affected by sepsis each year in the United States. The pillars of managing sepsis remain timely identification, initiation of antimicrobials while aiming for source control and resuscitation with a goal of restoring tissue perfusion. The focus herein is current evidence and best practice recommendations for state‐of‐the‐art sepsis care that begins in the ED.